The COVID‐19 pandemic dramatically reduced admissions of children with and without chronic conditions to general paediatric wards. (10th February 2021) - Gavish, Rachel; Levinsky, Yoel; Dizitzer, Yotam; Bilavsky, Efraim; Livni, Gilat; Pirogovsky, Avinoam; Scheuerman, Oded; Krause, Irit
Abstract: Aim: We examined the impact of the COVID‐19 pandemic on how many children were admitted to Israel's largest tertiary paediatric hospital and why they were admitted. Methods: Israel declared COVID‐19 a national emergency on 19 March 2020. This study examined daily hospital admissions to our three general paediatric wards during the COVID‐19 lockdown period from 20 March to 18 April 2020. These 258 admissions were compared with the 4217 admissions from the period immediately before this, 1 February to 19 March 2020, plus 1 February to 18 April in 2018 and 2019. We also compared why patients were admitted during the study period, and any pre‐existing conditions, with 638 children hospitalised during the same period in 2019. Results: The mean number of daily hospitalisations during the COVID‐19 lockdown period was 8.6, which was 59% lower than the 20.9 recorded during the other three periods before COVID‐19. There was a significant decrease in the number of patients admitted with infectious (74%) and non‐infectious (44%) aetiologies from 2019 to 2020, and these occurred among patients with (58%), and without (55%), pre‐existing medical conditions. Conclusion: The Israeli COVID‐19 lockdown had a dramatic effect on admissions to the paediatric wards of a tertiary hospital.